Parallel retention of Pdx2 genes in cartilaginous fish and coelacanths. - Mulley, J; Holland, P (Oxford University Press, 2010)
The Pdx1 or Ipf1 gene encodes an important homeodomain-containing protein with key roles in pancreas development and function. Mutations in human PDX1 are implicated in developmental defects and disease of the pancreas. Extensive research, including genome sequencing, has indicated that Pdx1 is the only member of its gene family in mammals, birds, amphibians, and ray-finned fish, and with the exception of teleost fish, this gene forms part of the ParaHox gene cluster along with Gsx1 and Cdx2. The ParaHox cluster, however, is a remnant of a 4-fold genome duplication; the three other ParaHox paralogues lack a Pdx-like gene in all vertebrate genomes examined to date. We have used bacterial artificial chromosome cloning and synteny analysis to show that the ancestor of living jawed vertebrates in fact had more ParaHox genes, including two Pdx genes (Pdx1 and Pdx2). Surprisingly, the two Pdx genes have been retained in parallel in two quite distantly related lineages, the cartilaginous fish (sharks, skates, and chimeras) and the Indonesian coelacanth, Latimeria menadoensis. The Pdx2 gene has been lost independently in ray-finned fish and in tetrapods.